Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/v13122486
|View full text |Cite
|
Sign up to set email alerts
|

Heparin and SARS-CoV-2: Multiple Pathophysiological Links

Abstract: Low molecular weight heparin, enoxaparin, has been one of most used drugs to fight the SARS-CoV-2 pandemic. Pharmacological properties of heparin recognize its specific ability, as with other oligosaccharides and glycosaminoglycan, to bind several types of viruses during their pass through the extracellular matrix of the respiratory tract, as well as its anticoagulant activity to prevent venous thromboembolism. Antithrombotic actions of enoxaparin have been testified both for inpatients with COVID-19 in regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Mechanical thromboprophylaxis is advised at a minimum [26,27]. Enoxaparin has the potential to bind certain viruses as they pass through the extracellular matrix of the respiratory tract [38]. This may provide additional benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical thromboprophylaxis is advised at a minimum [26,27]. Enoxaparin has the potential to bind certain viruses as they pass through the extracellular matrix of the respiratory tract [38]. This may provide additional benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin is extremely significant in the treatment of COVID19 patients due to its properties, mainly its similarity to heparan sulphate, which appears in a respiratory tract, its interactions with SARS-CoV-2 S protein, leading to viral adhesion inhibiting to the cell membrane [ 82 ], and its anti-inflammatory effects. Thanks to these properties, heparin may not only show its therapeutic effect as the anticoagulant, but also its protective role in acute pancreatitis or respiratory inflammations [ 83 , 84 , 85 ].…”
Section: Pancreatitis In Covid-19mentioning
confidence: 99%
“…On top of its antithrombotic action, heparin exerts an anti-inflammatory effect, a protective action on endothelial function [9], and a specific antiviral action in the extracellular matrix of tissues [10]. A short retrospective cohort analysis showed that the administration of low-molecular-weight heparin (LMWH) resulted in an increased number of lymphocytes and lower interleukin-6 (IL-6) levels compared to control patients, demonstrating an improvement in coagulation profiles and the restoration of immune functions.…”
Section: Introductionmentioning
confidence: 99%